Modeling, Docking, and Fitting of Atomic Structures to 3D Maps from Cryo-electron Microscopy - Allen, Gregory S. (2013)
Electron microscopy (EM) and image analysis offer an effective approach for determining the three-dimensional structure of macromolecular complexes. The versatility of these methods means that molecular species not normally amenable to other structural methods, e.g., X-ray crystallography and NMR spectroscopy, can be analyzed. However, the resolution of EM structures is often too low to provide an atomic model directly by chain tracing. Instead, a combination of modeling and fitting can be an effective way to analyze the EM structure at an atomic level, thus allowing localization of subunits or evaluation of conformational changes. Here we describe the steps involved in this process: building a homology model, fitting this model to an EM map, and using computational methods for docking of additional domains to the model. As an example, we illustrate the methods using an integral membrane protein, CopA, which functions to pump copper across the membrane in an ATP-dependent manner. In this example, we build a homology model based on the published atomic coordinates for a related calcium pump from sarcoplasmic reticulum (SERCA). After fitting this homology model to a 17 Å resolution EM map, computational software is used to dock a metal binding domain that is unique to the copper pump. Although this software identifies a number of plausible interfaces for docking, the constraints of the EM map steers us to select a unique solution. Thus, the synergy of these two methods allows us to describe both the location of the unknown metal binding domain relative to the other cytoplasmic domains and also the atomic details of the domain interface.